2018
DOI: 10.3847/1538-4357/aac104
|View full text |Cite
|
Sign up to set email alerts
|

The Productivity of Oxygenic Photosynthesis around Cool, M Dwarf Stars

Abstract: In the search for life around cool stars, the presence of atmospheric oxygen is a prominent biosignature, as it may indicate oxygenic photosynthesis (OP) on the planetary surface. On Earth, most oxygenic photosynthesizing organisms (OPOs) use photons between 400 and 750 nm, which have sufficient energy to drive the photosynthetic reaction that generates O2 from H2O and CO2. OPOs around cool stars may evolve similar biological machinery capable of producing oxygen from water. However, in the habitable zones (HZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 55 publications
3
36
0
Order By: Relevance
“…Instead, this hypothesis suggests that late-K and M-dwarf stars are unlikely to develop complex life until a more distant time in the future. Such a conclusion remains consistent with previous analyses that approach the problem from other perspectives (Loeb et al 2016;Ramjan et al 2017;Lingam and Loeb 2018a,b;Lehmer et al 2018).…”
Section: Testing the Proportional Evolutionary Time Hypothesissupporting
confidence: 92%
“…Instead, this hypothesis suggests that late-K and M-dwarf stars are unlikely to develop complex life until a more distant time in the future. Such a conclusion remains consistent with previous analyses that approach the problem from other perspectives (Loeb et al 2016;Ramjan et al 2017;Lingam and Loeb 2018a,b;Lehmer et al 2018).…”
Section: Testing the Proportional Evolutionary Time Hypothesissupporting
confidence: 92%
“…However, it was also argued therein that oxygenic photosynthesis might not evolve on planets around M-dwarfs as this process accords minimal competitive advantage. Lehmer et al (2018) investigated whether enough photons would be available to support an Earth-like biosphere on M-dwarf exoplanets, and found that many of them are incapable of doing so; see also Lingam and Loeb (2019d). In particular, if the maximum wavelength of PAR is specified to be 750 nm, none of the TRAPPIST-1 planets in the HZ appear to have the capacity for sustaining Earth-like biospheres.…”
Section: Photosynthesismentioning
confidence: 99%
“…The real issue, however, is that the net primary productivity on these worlds will be photonlimited in addition to other constraints imposed by access to nutrients and water. 8 Drawing an analogy with M-dwarf exoplanets (Lehmer et al 2018;Lingam & Loeb 2019d), it is possible that planets around brown dwarfs could likewise possess anoxic atmospheres (with negligible ozone layers) despite the presence of biospheres and thereby give rise to "false negatives" during searches for biological O 2 and O 3 .…”
Section: Discussionmentioning
confidence: 99%